Tuning mechanical behaviour by controlling the structure of a series of theophylline co-crystals. Issue 8 (31st January 2018) - Kakkar, Shubhangi; Bhattacharya, Biswajit; Reddy, C. Malla; Ghosh, Soumyajit
Abstract : Six new co-crystals of theophylline with some substituted carboxylic acids, amides and one active pharmaceutical ingredient (API) have been synthesized. Abstract : Six new co-crystals of theophylline with some substituted carboxylic acids, amides and one active pharmaceutical ingredient (API) have been synthesized. These new theophylline (THP) co-crystals with picolinamide (PIC), 3, 4-dichlorobenzoic acid (DCB), 4-chloro-3-nitrobenzoic acid (4Cl3NB), 4-fluoro-3-nitrobenzoic acid (4F3NB), p -hydroxybenzamide (HBEN) and acetazolamide (ACZ) were characterized by single crystal X-ray diffraction, differential scanning calorimetry and thermogravimetric analysis. THP–PIC, THP–DCB, THP–4Cl3NB and THP–4F3NB adopt 2D flat structures, while the other two, THP–ACZ and THP–HBEN, are 3D interlocked structures. The co-crystals having a 2D structure show shearing behaviour on application of a mechanical stress in a qualitative sense, whereas the interlocked crystals are associated with brittleness in nature. This series of co-crystals give a better picture of the structure–property correlation on the basis of inherent crystal packing. The presence of strong intralayer interactions and weak interlayer interactions in 2D layered crystals is crucial in imparting softness in THP–DCB, THP–PIC, THP–4Cl3NB and THP–4F3NB.